Khiyar Aib Menurut Pandangan Pimpinan Cabang Istimewa Muhammadiyah Arab Saudi - Anas, Muh Fauzi; Bakri, Mukhlis; Hijaz, M. Chiar (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The Special Branch Leadership is a group of Muhammadiyah members and its supporters based in a city or country outside the territory of the Republic of Indonesia. This group is recognized and established by the Central Leadership of Muhammadiyah. The establishment of the Special Branch can be initiated by Muhammadiyah members or supporters in that location, or based on a direct initiative from the Central Leadership of Muhammadiyah.This research aims to understand the views of the Special Branch Leaders of Muhammadiyah in Saudi Arabia regarding Khiyar Aib in the context of marriage, as well as to comprehend what faults may entitle someone to the right of khiyar in marriage. This research employs a qualitative method. Data is gathered through a series of interviews supported by documentation. The subjects of the study include the daily management body and the chairpersons of the special branch leadership council of Muhammadiyah in Saudi Arabia. To collect data, the author utilizes various techniques, including observation, interviews, and documentation. The research is conducted in the city and district of Madinah Al-Munawwarah. According to the leadership of the special branch of Muhammadiyah in Saudi Arabia, the results of this research state that khiyar based on the faults of one's spouse is considered lawful and in accordance with Shariah. The khiyar right can also be brought before the court by both parties, whether male or female. Although this khiyar right remains relevant for application in contemporary times, it is crucial to exercise it with caution and not to use it as a pretext to undermine the sanctity of marriage. Additionally, it is important not to apply it hastily, so as not to create uncertainty in marital relationships.